Publishing clinical prActice GuidelinEs (PAGE): Recommendations from editors and reviewers. Issue 2 (29th June 2022) - Yang, Nan; Zhao, Wei; Qi, Wenan; Yao, Chen; Dong, Chongya; Zhai, Zhenguo; Chen, Tong; Liu, Enmei; Li, Guobao; Long, Youlin; Wang, Xinyi; Wang, Zijun; et al.
Abstract: Transparency Ecosystem for Research and Journals in Medicine (TERM) Working Group summarized the essential recommendations that should be considered to review and publish a high‐quality guideline. These recommendations from editors and reviewers included the ten components of essential requirements: systematic review of existing relevant guidelines, guideline registration, guideline protocol, stakeholders, conflicts of interest, clinical questions, systematic reviews, recommendation consensus, guideline reporting, and external review. TERM Working Group abbreviates them as PAGE (essential requirements for Publishing clinical prActice GuidelinEs), recommends guideline authors, editors, and peer reviewers use them for high‐quality guidelines.